Investigating the Everyone Is Teacher Here (ETH) Learning Model on Biology Learning Outcomes - Nofriadi, Nanang; Yestin, Yoki (Yayasan Nurul Yakin Bunga Tanjung, 2022)
The purpose of this research is to prove whether there is an effect of using the Everyone Is A Teacher Here (ETH) learning model on the learning outcomes of class X students at SMA Tuah Kemuning. This research is a quantitative study using true experimental design postest only control design. Sampling using the Cluster Random Sampling technique in order to obtain class XI IPA 1 as the experimental class and class XI IPA 2 as the control class. The data collection instrument used a multiple choice test. Based on the analysis of data calculations, the average value of student learning outcomes in the experimental class was 80.8, while for the control class the average student learning outcomes were 70.24. Based on the results of data analysis, it was found that student learning outcomes with a value of t0 ≥ ti were 2.01 <3.91> 2.68 with a large effect size of 1.15 or 86%. So, it can be concluded that there is an effect of using the ETH model on the learning outcomes of class XI students at SMA Tuah Kemuning. The results of this study suggest that teachers apply the ETH model as a learning model for further material.